Why is child malnutrition lower in urban than rural areas?: evidence from 36 developing countries - Smith, Lisa C.; Ruel, Marie T.; Ndiaye, Aida (International Food Policy Research Institute, 2004)
While ample evidence documents that urban children generally have better nutritional status than their rural counterparts, recent research suggests that urban malnutrition is on the rise. The environment, choices, and opportunities of urbanites differ greatly from those of rural dwellers' from employment conditions to social and family networks to access to health care and other services. Given these differences, understanding the relative importance of the various determinants of child malnutrition in urban and rural areas -- and especially whether they differ -- is key to designing context-relevant, effective program and policy responses for stemming malnutrition. This study uses Demographic and Health Survey data from 36 developing countries to address the question of whether the socioeconomic determinants of child nutritional status differ across urban and rural areas. The purpose is to answer the broader question of why child malnutrition rates are lower in urban areas. The socioeconomic determinants examined are women's education, women's status, access to safe water and sanitation, and household economic status. The analysis finds little evidence of differences in the nature of the socioeconomic determinants or in the strength of their associations with child nutritional status across urban and rural areas. As expected, however, it documents marked differences in the levels of these determinants in favor of urban areas. Large gaps in favor of urban areas are also found in the levels of key proximate determinants of child nutritional status, especially maternal prenatal and birthing care, quality of complementary feeding, and immunization of children. The conclusion is that better nutritional status of urban children is probably due to the cumulative effect of a series of more favorable socioeconomic conditions, which, in turn, seems to lead to better caring practices for children and their mothers. Given that the nature of the determinants of child nutritional status is largely the same across urban and rural areas, the same program and policy framework can be used to stem malnutrition in both. Efforts to alleviate the most critical socioeconomic constraints specific to the different environments should continue to be prioritized.